Chrysalis eaudiobook A thriller. - Child, Lincoln (Jeremy Logan, 2022)
A blockbuster new thriller from #1 New York Times bestselling author Lincoln Child, centered on a dominant tech company—Chrysalis—whose groundbreaking virtual reality technology is redefining the way we live...and possibly introducing a catastrophic danger to the world. Like millions of people around the world, Jeremy Logan (famed enigmalogist, or investigator of unexplained things) has grown to rely on his incredible new tech device. Made by Chrysalis, the global multibillion dollar tech company, the small optical device connects people in a stunning new way, tapping into virtual reality for the first time on a wide scale. And yet, when Logan is summoned by Chrysalis to investigate a disturbing anomaly in the massive new product rollout, Logan is shocked to see the true scope of the massive company. He also quickly realizes that something in Chrysalis’s technology is very wrong, and could be potentially devastating. The question is what, and where, is the danger coming from? In Lincoln Child’s wildly inventive new novel, high tech comes to life alongside the myriad dangers it poses, making for one of Child’s most infectious, entertaining thrillers to date.